2016
DOI: 10.1155/2016/4342892
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene Production on Enzymatic Hydrolysate of Peanut Hull Using Different Pretreatment Methods

Abstract: The present study is about the use of peanut hull for isoprene production. In this study, two pretreatment methods, hydrogen peroxide-acetic acid (HPAC) and popping, were employed prior to enzymatic hydrolysis, which could destroy the lignocellulosic structure and accordingly improve the efficiency of enzymatic hydrolysis. It is proven that the isoprene production on enzymatic hydrolysate with HPAC pretreatment is about 1.9-fold higher than that of popping pretreatment. Moreover, through High Performance Liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The total phenolic contents of the samples were determined using a microtube test (Spectroquant, Merck) closely followed by a 4-aminoantipyrine colorimetric measurement (Monlau et al, 2015). The TS content were determined by drying samples to constant weight at 105°C while for VS, known weights of dried samples were ignited to constant weight at 575 ± 25°C (Wang et al, 2016). Soluble sugars (sucrose and inulin) were extracted using a mild acid hydrolysis protocol after which the anthrone method was used to do further quantification (Dahunsi et al, 2017b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total phenolic contents of the samples were determined using a microtube test (Spectroquant, Merck) closely followed by a 4-aminoantipyrine colorimetric measurement (Monlau et al, 2015). The TS content were determined by drying samples to constant weight at 105°C while for VS, known weights of dried samples were ignited to constant weight at 575 ± 25°C (Wang et al, 2016). Soluble sugars (sucrose and inulin) were extracted using a mild acid hydrolysis protocol after which the anthrone method was used to do further quantification (Dahunsi et al, 2017b).…”
Section: Methodsmentioning
confidence: 99%
“…In Brazil (South America), an annual production of around 320,000 tons was generated in 2014 also giving more than 90,000 tons of the hulls (Polachini et al, 2016). In China (Asia), annual production is about 13 million tons with approximately 3.64 million tons hulls being generated (USDA, 2014;Wang et al, 2016). In Nigeria (Africa), total production of 8.7 million metric tons was recorded in Nigeria alone in 2011 from a total harvested area of 9.04 million ha (FAOSTAT, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, as the demand for oil is ever-increasing, there is an urgent need to breed new peanut varieties with high yields, a characteristic that is dependent on pod size. Previous research has shown that pod size is mainly determined by quantitative trait loci (QTL), and several of these have been identified (Fonceka et al, 2012 ; Chen et al, 2016 , 2017 ; Wang et al, 2016 ; Luo et al, 2017 ). Earlier work has shown that peanut genotypes from different backgrounds harbor distinct QTLs; thus, the primary characteristics of peanut which distinguish this plant from others include aerial flowering, a gynophore (peg) that elongates gravitropically, and subterranean fruiting.…”
Section: Introductionmentioning
confidence: 99%
“…A typical peanut pod is comprised of three parts, a hull, a seed coat (or testa), and an embryo; of these, the hull forms a protective layer surrounding the seed, which itself functions to protect the endosperm and shield the embryo from external stresses. The hull of a peanut is composed of 46.8% holocellulose, 43.4% Klason lignin, 5.8% ash, and 4.0% organic solvent extracts (OSE) (Wang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%